Matrock’s Burger / Muhammad Iqbal Kamarulzaman - Muhammad Iqbal, Kamarulzaman (2020)
Matrock’s burger is the named of this business. Like you can see the name, This business are about selling burgers. This business are planning to open at the Semenyih near to University of Nottingham. The main customers that are gonna be targets are the students and the household near of the area. This business are using of foodtruck. The places to make a burger are not to big but it is enough to make an amazing burgers for the customers. The team to build this business are only three people that have their own responsibility. To make a burger and the places to dine-in should have got enough equipment to cooking and the furniture. The products have their speciality and unique than another burgers stall does not have. To make a burger that have many ingredient that should have such as sauce, the meat, burger bread and etc. At last, Financial plan are the most important to organized and planning the business to being positive and gain a profit for the business. A cash flow statment is identified the cash annually. To know if the business at what month there got profit ordeficit. If there are deficit, a proper plan shoula taken to get the business positive again.